Image Encryption using RSA Algorithm with Biometric Recognition (International Journal of Engineering and Computer Science, 2018)
— In the fast evolution of digital data exchange, security of any information becomes much important in data storage and transmission. Due to the increasing use of images in various fields, it is essential to protect the confidential image data from unauthorized access. Biometric identification is an actively growing area of research and is widely used in application fields like E-commerce, E-banking, E-passports, E-licences and security applications. In recent years, Face recognition becomes one of the popular biometric identification systems used in identifying or verifying individuals and matching it against library of known faces. Also it finds its application in wide variety of areas like criminal identification, human - computer interaction, security systems, credit- card verification, teleconference, image and film processing. This paper suggests a secure encryption of medical images along with an automated face recognition system based on extracting the features from the input face image. For encryption process, RSA algorithm is used. Feature extraction process in the face image is performed by locating the position of eyes, nostrils and mouth and determining the distances between those regions. From the extracted features, a database is created for known individuals. A virtual neural network is created based on Extreme Learning Machine (ELM). This network verifies whether the individual is a known user or an intruder.